Exploring the Integration Path of Intangible Cultural Heritage Revitalization and Commercial Innovation: A Case Study of the "Rhythm of Dye: Blind Collection" Tie-Dye Blind Box Project - Bai, Zong tian; Zhang , Huiyu; Meng, Ye; Wang , Hui (International Journal of Multidisciplinary Research, 2026)
Against the backdrop of cultural industry innovation and consumption upgrading, the revitalization of Intangible Cultural Heritage (ICH) faces a transitional need from "protective inheritance" to "innovative development." Taking the "Dye-Charm Blind Collection" tie-dye blind box project as a case study and employing qualitative research methods, this paper systematically explores innovative pathways for integrating ICH with the blind box economy. The research finds that the project achieves the commercial transformation of tie-dye cultural capital through a three-dimensional innovation system encompassing "product reconstruction (cultural symbols + functional extension + experience design), technological empowerment (process optimization + digital design + standardized production), and ecosystem construction (online-offline integration + domestic-overseas markets + experience-sales synergy)." Practice demonstrates that the project has not only achieved significant economic benefits (projected revenue of 1.7 million RMB for 2025, with a repurchase rate of 40%) but also generated positive social impacts in areas such as rural revitalization and cultural dissemination. This study proposes that ICH revitalization should, based on Cultural Capital Theory and Scene Consumption Theory, construct a sustainable development model of "culture-commerce-society" synergistic symbiosis, providing theoretical reference and practical guidance for the innovative development of ICH.